An artist of the floating world - Ishiguro, Kazuo, 1954- (Vintage International (Series), 1989)
World War II is over and Japan sets about rebuilding her shattered cities. Masuji Ono, an aging painter, looks back over his life and assesses a career that coincided with the rise of Japanese militarism.